Sensory Decline and Cardiovascular Risk in Older Adults: Psychosocial and Communication-Mediated Pathways – A narrative review - Zienkiewicz, Damian; Kozicki, Maciej Jakub; Kostro, Julia Maria; Makulec, Gabriela; Domosud, Karolina; Papież, Magdalena; Jędra, Zofia; Libera, Anna; Bartkiewicz, Karolina; Novik, Lizaveta (Quality in Sport, 2026)
Background: Hearing loss affects roughly 65% of adults aged 70 and older, vision impairment 20–30%, and dual sensory loss becomes more common with age. Meta-analyses show that these forms of sensory decline are associated with higher risks of hypertension, stroke, coronary heart disease, and cardiovascular mortality, even after adjustment for traditional cardiovascular risk factors. Shared vascular pathology explains part of these associations, but psychosocial and communication pathways may also contribute. Aim: To summarize evidence on psychosocial and communication-mediated mechanisms linking sensory decline to cardiovascular risk in older adults and to outline an integrated conceptual model. Material and Methods: A narrative review was conducted using targeted searches of PubMed and Google Scholar. Meta-analyses, cohort studies, and relevant qualitative and mechanistic literature were included. Findings were synthesized qualitatively. Results: Sensory impairment increases cognitive and communicative demands, which may heighten chronic stress and influence neuroendocrine and inflammatory pathways linked to cardiovascular disease. Reduced sensory input limits social participation and contributes to social isolation and loneliness, both established cardiovascular risk factors. In healthcare settings, communication barriers can impair symptom reporting, treatment adherence, and management of complex cardiovascular regimens. These pathways complement biological mechanisms and help explain persistent associations between sensory decline and cardiovascular outcomes. Conclusions: Psychosocial and communication mechanisms appear to be modifiable contributors to cardiovascular vulnerability in older adults with sensory impairment. Potential strategies include routine sensory screening, communication-accessible care, and interventions addressing isolation and stress. Randomized trials are needed to determine whether sensory interventions can reduce cardiovascular events.